Buyang Huanwu Decoction promotes the neurological recovery of traumatic spinal cord injury via inhibiting apoptosis, inflammation, and oxidative stress - Xu Li; Yingjun Song; Yang Yang; Guofu Zhang (Immunity, Inflammation and Disease, 2023)
Abstract Background The incidence rate of spinal cord injury (SCI) is increasing, and the mortality or disability rate caused by SCI remains high in the world. Buyang Huanwu Decoction (BYHWD) is a kind of Traditional Chinese medicine, and it is believed to be effective in several kinds of nervous system diseases. Whether BYHWD could improve SCI and the potential function mechanism remain unclear. Methods SCI animal model was established by damaging T10 spinal cord. Animals experiments included five groups as follows: Sham, SCI, SCI+BYHWD, SCI+mesenchymal stromal cells (MSCs), and SCI+BYHWD+MSCs. H2O2‐treated cells (100 µM, 6 h) were used to simulate SCI damage in vitro, which included five groups as follows: control, H2O2, H2O2+BYHWD, H2O2+MSCs, and H2O2+BYHWD+MSCs. The behavioral function was evaluated with Tarlov and inclined plated test score. Western blot analysis and immunohistochemical staining were used to detect protein expression. The levels of superoxide dismutase (SOD), catalase (CAT), malondiadehyde (MDA), interleukin (IL)‐1β, tumor necrosis factor‐α, and IL‐6 in serum were measured with commercial enzyme‐linked immunosorbent assay kits. terminal deoxynucleotidyl transferase dUTP nick end labeling staining and flow cytometry were performed to measure apoptosis in vivo and in vitro levels. Gene expression profiling analysis was performed to analyze differential expression genes. Results BYHWD suppressed apoptosis and accelerating cell proliferation after SCI. Recovery of neurofunction, inhibition of inflammatory response, and oxidative condition were achieved by BYHWD and MSCs. The expression levels of gp130/Janus kinase/signal transducers and activator of transcription (JAK/STAT) were suppressed by BYHWD and MSCs, both in vivo and in vitro. BYHWD and MSCs markedly promoted cells viability and inhibited apoptosis. Greater gene expression difference was observed between group control and H2O2 through gene expression profiling analysis. The recovery effects of traumatic SCI by BYHWD were similar to MSCs, and synergies effects were observed in several items. Conclusion BYHWD could increase Tarlov score and Basso, Beatie, and Bresnahan functional score, inhibit apoptosis, inflammatory response, and oxidative condition after SCI. The expression level of gp130/JAK/STAT axis was suppressed by BYHWD. BYHWD might be a new therapeutic strategy for the prevention or treatment of SCI.